2022
DOI: 10.1108/ijchm-10-2021-1238
|View full text |Cite
|
Sign up to set email alerts
|

How organizational justice in the hospitality industry influences proactive customer service performance through general self-efficacy

Abstract: Purpose Based on social exchange theory (SET) and conservation of resources (COR) theory, this study aims to examine the unique combined impact of procedural justice (PJ) and distributive justice (DJ) on proactive customer service performance (PCSP) and general self-efficacy (GSE) in the hospitality industry. It also estimates these variables’ joint effect on PCSP controlling GSE. Design/methodology/approach The study’s results were derived from a sample of 380 frontline supervisor–subordinate dyads, placed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 69 publications
1
22
0
Order By: Relevance
“…Organizational justice theory refers as " how applicants react to organizations using job application portal " (Madera, 2012). Even though organizational justice is generally split into 3 subgroups: distributive (i.e., the fairness about what one obtains as a result of decisions), procedural (i.e., the perceived fairness of structured decision-making procedures), and interactional (i.e., the impact on the interpersonal benefit received throughout processes installations), recent studies suggest that a sense of fair play is more significant predictors of responses than a value of justice (Abuelhassan & AlGassim, 2022). Organizational justice is dealing with the perceived selection of objectives and processes in firms, such as workplace rules, encounters, and protocols.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Organizational justice theory refers as " how applicants react to organizations using job application portal " (Madera, 2012). Even though organizational justice is generally split into 3 subgroups: distributive (i.e., the fairness about what one obtains as a result of decisions), procedural (i.e., the perceived fairness of structured decision-making procedures), and interactional (i.e., the impact on the interpersonal benefit received throughout processes installations), recent studies suggest that a sense of fair play is more significant predictors of responses than a value of justice (Abuelhassan & AlGassim, 2022). Organizational justice is dealing with the perceived selection of objectives and processes in firms, such as workplace rules, encounters, and protocols.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is frequently acknowledged as a key component in users' adaption to new technologies. People adjust to a given technology due to specific motives, according to the organizational justice theory (Abuelhassan & AlGassim, 2022). According to this notion, perceived usefulness is a consumer's external motive that motivates them to weigh the benefits of a certain technology (Kleanthous et al, 2022).…”
Section: Relative Advantagementioning
confidence: 99%
“…Leaders are often at the core of business success stories and failures at the societal level. All firms are particularly in need of leaders who consolidate insights and applications of business ethics, CSR and sustainability into their internal cultures (Abuelhassan and AlGassim, 2022; Aboramadan et al , 2020; Elbaz and Haddoud, 2017; Frangieh and Yaacoub, 2017; Herhausen et al , 2017). Mattila and Hanks (2012) asserted that firms spend time and money to position themselves as socially responsible to satisfy their customers in a highly competitive marketplace.…”
Section: Introductionmentioning
confidence: 99%
“…Although previous research has identified the negative impacts of LAH, it has received less attention in the hospitality context. As hospitality operations rely heavily on employees’ excellent customer service (Abuelhassan and AlGassim, 2022; Hu et al , 2022; Sarwar et al , 2021), their interactions with their leaders and any potential negative outcomes could lead to negative performance. Meanwhile, the hospitality work environment is becoming increasingly challenging and stressful [e.g.…”
Section: Introductionmentioning
confidence: 99%